(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the nature of electronic document circulation, its advantages and implementation based on modern technologies. Consideration will be given to how electronic document circulation will create convenience for enterprises, state organizations and individuals. Also, the main stages of the introduction of electronic document circulation and the ways of its effective organization are considered.